2017
DOI: 10.5897/ajb2016.15688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sesame (Sesamum indicum L.) germplasm collection of Tamil Nadu for -linolenic acid, sesamin and sesamol content

Abstract: A germplasm collection of Tamil Nadu comprising of nine varieties and six landraces were analyzed for their ω3 fatty acid content, lignans such as sesamin and sesamol. The percentage of ALA ranges from 0.1 to 0.55%. A wide variation was observed in sesamol content. The highest sesamol content of 0.547 mg/g was found in a variety SVPR1. The sesamin content ranged between 2.03 and 6.45 mg/g. A negative relationship was observed between total oil content and ALA. White sesame seeds had higher sesamol content wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Wang et al [ 16 ] reported that seed sesamin and sesamolin mainly ranged from 0.88~11.05 mg/g and 0.93~6.96 mg/g, respectively, in a core collection conserved in China. In some Indian and Thai germplasms, seed sesamin ranged from 0.08~6.45 mg/g and 1.63~7.23 mg/g, respectively, and sesamolin from 0.28~3.76 mg/g and 0.48~2.25 mg/g, respectively [ 19 , 40 , 41 ]. The phenotype data from the two locations showed a significant positive correlation between sesamin and sesamolin content.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 16 ] reported that seed sesamin and sesamolin mainly ranged from 0.88~11.05 mg/g and 0.93~6.96 mg/g, respectively, in a core collection conserved in China. In some Indian and Thai germplasms, seed sesamin ranged from 0.08~6.45 mg/g and 1.63~7.23 mg/g, respectively, and sesamolin from 0.28~3.76 mg/g and 0.48~2.25 mg/g, respectively [ 19 , 40 , 41 ]. The phenotype data from the two locations showed a significant positive correlation between sesamin and sesamolin content.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that white sesame seeds had higher levels of lignans than the other sesame genotypes. Likewise Shi et al [ 77 ], Dar et al [ 60 ], Muthulakshmi et al [ 78 ], and Kim et al [ 74 ] found that black-colored seeds contained larger quantities of sesamin and sesamolin contents. Dar et al [ 79 ] reported an average sesamolin content of 1.56–3.28 mg/g in black sesame, slightly higher than the range of 0.46–1.67 mg/g found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Sesame seed is a rich source of dietary lignans. [15] Lignan (sesamol, sesamin, and sesamolin) profile was identified in sesame seeds. [16][17] SM is the main reason for the oxidative stability of sesame seed oil.…”
Section: Introductionmentioning
confidence: 99%